Adaptive Reuse of Heritage Buildings - Bullen, Peter; Love, Peter (Emerald, 2011)
Purpose – There is growing acceptance that heritage buildings are an important element of Australia's social capital and that heritage conservation provides economic, cultural and social benefits to urban communities. The decision whether to reuse a building entails a complex set of considerations including location, heritage, architectural assets, and market trends. The role of building conservation has changed from preservation to being part of a broader strategy for urban regeneration and sustainability. A growing body of opinion supports the view that adaptive reuse is a powerful strategy for handling this change. Urban development and subsequent redevelopment has a significant impact on the environment and the purpose of this paper is to investigate how the conservation of heritage buildings may contribute to a more sustainable urban environment. Design/methodology/approach – This paper examines the views and experiences of architects, developers and building managers who have been involved with the adaptive reuse of heritage buildings. In total, 60 semi‐structured interviews were drawn from this stakeholder group to investigate their current understanding of the sustainability issues associated with the adaptive reuse of heritage buildings. Findings – The subsequent data show that despite many positive outcomes in terms of sustainability, the adaptive reuse of heritage buildings is considered to create many problems; not the least of which is whether heritage buildings are icons that should be conserved or whether they are in fact eyesores and unviable for adaptive reuse. Originality/value – The contribution of heritage buildings to the three tenets of sustainability has not previously been explored comprehensively and as a result there is a conflict of interest between the preservation of heritage values and progression of the sustainable urban design agenda.